2006
DOI: 10.1007/s11113-006-9006-5
|View full text |Cite
|
Sign up to set email alerts
|

Neighbors and neighborhoods: effects on marriage timing

Abstract: Studies of neighborhoods can benefit from data and theoretical frameworks that allow them to examine the differences between neighborhoods and neighbors. Without this distinction, it is unclear if it is characteristics of the people or the place that are associated with individual outcomes. Using data from the Chitwan Valley Family Study, I explore the differences between neighbors and neighborhoods and their associations with marriage timing. I hypothesize three mechanisms whereby neighbors influence individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 66 publications
1
27
0
Order By: Relevance
“…Attitude of the neighbors have also been found to influence marriage decisions. Yabiku (2006) has explored the role of neighbors and neighborhood in timing of marriage in south-central Nepal. These variables have not been given adequate attention in the literature due to lack of availability of data.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Attitude of the neighbors have also been found to influence marriage decisions. Yabiku (2006) has explored the role of neighbors and neighborhood in timing of marriage in south-central Nepal. These variables have not been given adequate attention in the literature due to lack of availability of data.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Such associations that are indicative of externality effects of education have also been reported in fertility studies from other regions (Hirschman and Young 2000) and in investigations of fertility desires (Moursund and Kravdal 2003;Baschieri 2007) or contraceptive use (Benefo 2006(Benefo , 2010DeRose, Wu, and Dodoo 2010;McNay et al 2003;Moursund and Kravdal 2003;Stephenson et al 2007;Stephenson, Beke, and Tshibangu 2008) in various developing countries, with a variety of additional factors included (more or less appropriately) in the models. There are also studies, however, where associations have not shown up (Gupta and Mahy 2003;Yabiku 2006). Similarly, community socioeconomic resources may affect individual health and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…10 Socializing with others may raise aspirations and change behaviors. 7,8,11 If it is true that individuals socialized in a more modern way have more freedom to choose their partners, we might expect to see change in the nature of relationships between couples. For example, people may modify their sexual behavior.…”
Section: Modelingmentioning
confidence: 99%
“…For example, a modern community may be more open to accepting individuals' freedom to choose their spouse. 11,22 Changes in family formation are also closely related to changes in family systems. Early marriage is typical in a society where the wedding serves as an alliance between families.…”
Section: Limitationsmentioning
confidence: 99%